bonjour
2 x(3 x - 1) + ( 5 x + 2) ( 3 x - 1)
= ( 3 x - 1) ( 2 x + 5 x + 2)
= ( 3 x - 1) ( 7 x + 2)
x² + 9 = 0
( x + 3) ( x - 3) = 0 donc l'un des 2 facteurs est nul donc x = - 3 ou 3
2 x + 4 = 5 x - 2
2 x - 5 x = - 2 - 4
- 3 x = - 6
x = 6/3 = 2
( 2 n + 5) ( 2 n - 5)
développement = 4 n² - 10 n + 10 n - 25 = 4 n² - 25
B ) ( 4 x + 3) ( 2 x + 5) = 8 x² + 20 x + 6 x + 15 = 8 x² + 26 x + 15
pour x = 0 , B = 15
C) x( 4 - 6 x ) + 3 x² + 5 x - 9
= 4 x² - 6 x² + 3 x² + 5 x - 9
= x² + 5 x - 9
pour x = - 2 , C = (-2)² + 5*-2 - 9 = 4 - 10 - 9 = - 15
0.00723 = 7.23 x 10 ⁻³